Aplicaciones clínicas de la bola de bichat en los defectos intraorales: revisión sistemática (2023)
The bichat ball is a mass of fat, surrounded by connective tissue. It was described by Xavier Bichat in 1802. It has a body and four extensions: buccal, pterygoid, superficial temporal and deep temporal, it is also surrounded by salivary glands, parotidean duct, buccal artery, facial artery and vein. Objective: To carry out a systematic review between 2012-2023 of the clinical dental applications of Bichat's ball in intraoral defects. Methodology: Qualitative systematic review, retrospective descriptive research. Initially, the research question arises: What are the clinical applications of the Bichat ball in intraoral defects? Then, the systematic research protocol is elaborated based on the Cochrane Handbook and the book “Fundamentos Das Revisões Sistemáticas Em Odontologia” (Honorio & Santiago, 2018). Then, we proceed with the registration in the Prospero international prospective registry. Next, we continue with the search in 6 databases: Cochrane, pubmed, embase, scopus, science direct and scielo with the terms that yielded the PICO question: adults, Bichat fat pad, oral defects and dentistry in English and Spanish, collecting articles with the inclusion and exclusion criteria. The selection of the articles is plotted with Prisma flowchart and the organization of the included research is tabulated in an Excel matrix. Then, the qualitative analysis is executed with the modified McEvoy instrument (Honorio & Santiago, 2018). Finally, the global analysis and the writing of results is oriented from the Prisma-P 2020 guide (Page, McKenzie, & Bossuyt, 2021). Expected results: The description of the clinical applications in which the Bichat ball can be used to correct intraoral defects. Conclusion: Knowing the intraoral clinical applications of the Bichat ball can allow the correct use of the Bichat ball to treat intraoral defects in the same patient.